Hybride Rechtssubjektivität Die Rechte der "Natur oder Pacha Mama" in der ecuadorianischen Verfassung von 2008 - Gutmann, Andreas (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2021)
Currently, there is a debate in numerous places around the world whether rights of nature could be an adequate legal tool for dealing with the environmental crises of our time. This paper deals with the world's first constitutional recognition of such rights in the Ecuadorian Constitution of 2008 and takes a theoretical approach based in particular on postcolonial theories. It interprets these new rights as a hybrid right that provides general impulses for thinking about legal subjectivity and points in the direction of a participatory and inclusive model of rights that foregrounds the interdependencies and interrelatedness of legal subjects.